Use of content mastery service using role playing approach improve student's emotional intelligence - Meirizka Liyani Putri; Taufik Taufik; Frischa Meivilona Yendi; Verlanda Yuca (SCHOULID: Indonesian Journal of School Counseling)
Emotional intelligence is the ability possessed by individuals to be able to recognize, understand, manage and manage emotions and understand the emotions of others. There are many problems that arise related to emotional intelligence, especially in the school environment. To be able to overcome this and increase the emotional intelligence of BK teacher students can carry out content mastery services that aim to help students develop and learn new aspects or competencies related to emotional intelligence. Implementation of content mastery services can also be done with a role playing approach by playing the role associated with increasing emotional intelligence.